Aid projects: The effects of commodification and exchange. (February 2020) - Freeman, Scott; Schuller, Mark
Highlights: Humanitarian and development aid largely revolve around the project form. Projects have become commodities exchanged by donors and contractors. The project market is marked by an exchange of funding for project documentation. Contractor funding priorities privilege project exchange value over beneficiary needs. The need for success and visibility distorts design, implementation, and evaluation. Abstract: International aid work has been increasingly oriented around the administrative form of the aid project. Aid projects are financial and temporal delineations used for the planning, implementation, and reporting of aid work. Originating as a budgetary reform, the project has grown to become an important unit of conceptualization for donors, subcontracting NGOs, aid workers, and the recipients of development projects. As the project has become the dominant form of disbursing aid, what effects does this administrative form have on contemporary humanitarian and development work? A growing literature on the project form combined with ethnographic research on humanitarian and development aid in Haiti demonstrates how the project is not only an administrative unit but has become a principal product of aid work. Framing the project as a commodity produced within the aid industry illuminates the centrality of exchange, rather than donation, at the heart of the aid industry. Project documents, produced in order to account for implementation, assume the form of a commodity as they are exchanged for aid funding. Accordingly, project documents have a particular exchange value within the aid industry. One of the more prevalent effects of project-based aid is that for NGOs and subcontractors, this exchange value can take precedence over services provided to beneficiaries. In order to compete in the market for projects, sub-contracting organizations seek visibility and documentation, which may come at the expense of service provision. This affects the way in which projects are both implemented and evaluated. By illustrating the impacts of the administrative form of aid, this research argues for a more focused line of research interrogating the politics of the project.